Kazakhstan Growth Slows as External Pressures Rise : Kazakhstan Economic Update, Fall 2014 - World Bank Group (Washington, DC, 2014)
Kazakhstan is experiencing slower economic growth in 2014 due to negative supply- and demand-side effects. The Kazakh authorities are using expansionary fiscal and monetary policies to stimulate domestic demand. An uncertain global economic environment and regional geopolitical tensions pose risks to the economic outlook of Kazakhstan. If the economic slowdown starts to have a negative effect on the labor market, the government has instruments to mitigate its impact on the most vulnerable population. The government has identified a set of reforms that are expected to help diversify the economy and expand the non-oil sector. They have launched a major program of support for the development of small- and medium-sized enterprises, including by addressing the constraints related to access to credit. They are also working to improve the national regulatory and governance framework that will enhance the transparency and efficiency of economic transactions, facilitate private sector participation, and improve service delivery to the population. Ongoing reforms in customs administration and the courts are part of its reform agenda.